On multidimensional central limit theorem - Sazonov, V. V. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. В. Сазонов. К многомерной предельной теореме V. Sazonovas. Daugiamatės ribinės teoremos klausimu